Prolonging Postoperative Hospitalization in Patients with Recurrent Tonsillitis to Reduce the Risk of Bleeding After Tonsillectomy - Fatih Öner; Elif Kaya Çelik; Fatma Atalay (The Turkish Journal of Ear Nose and Throat)
Objective: This study aims to investigate the effect of lengthening early postoperative hospitalization on post-tonsillectomy bleeding and retrospectively analyzes patients who were operated on for a recurrent tonsillitis diagnosis.Materials and Methods: The study includes a total of 92 patients who underwent a tonsillectomy for a recurrent tonsillitis diagnosis. The patients were divided into two groups: those discharged on postoperative day 1 (Group A), and those hospitalized for a more extended period (Group B). Both groups were compared in terms of bleeding after the tonsillectomy.Results: In both groups, none of the patients aged 15 or under presented with post-tonsillectomy bleeding. For patients over the age of 15, no re-admission to the hospital with postoperative bleeding occurred in Group B, while 10 patients (10.9%) from Group A presented with complaints of bleeding and were re-hospitalized.Conclusion: Extending the early hospitalization period to at least two days in tonsillectomies to be performed for recurrent tonsillitis, especially for late adolescents and adult patients, may reduce the likelihood of a revisit with post-tonsillectomy bleeding.